Peripheral and central substance P expression in rat CFA-induced TMJ synovitis pain. (July 2019) - Xu, Liqin; Jiang, Henghua; Feng, Yaping; Cao, Pinyin; Ke, Jin; Long, Xing
Synovitis contributes to temporomandibular joint (TMJ) pain, nevertheless, the detailed nociceptive mechanism remains unclear. In this study, a rat model of TMJ synovitis was induced by intra-articular injection with complete Freund's adjuvant (CFA). After CFA-induced synovitis, pain behaviors were observed. Then, TMJ, trigeminal ganglion, and trigeminal nucleus caudalis (TNC) tissues were collected, and immunohistochemistry was used to detect the expression of substance P (SP) and protein gene product 9.5 (PGP9.5) in the synovium tissue. Furthermore, the gene expression level of SP and PGP9.5 in synovium was detected by reverse transcription-polymerase chain reaction (RT-PCR). Afterwards, the expression of SP in the trigeminal ganglion and TNC and c-fos in the TNC was detected by immunohistochemistry. Compared with the control group, the expression of SP and PGP9.5 nerve fibers density and gene levels of them in the synovium tissue were significantly increased in CFA-induced TMJ synovitis rats. Similarly, SP expression in the trigeminal ganglion and TNC, and c-fos expression in the TNC were also obviously increased in CFA-induced TMJ synovitis rats. Collectively, CFA-induced rat TMJ synovitis resulted in obvious pain. This nociceptive reaction could be attributed to the augmented quantity of SP and PGP9.5 positive-stained nerve fibers distributed in the inflammatory synovium as well as enhanced SP expression in the trigeminal ganglion and TNC tissue. c-fos expression in the rat TNC illustrates CFA-induced TMJ synovitis can evoke the acute pain.